Attachment patterns and their relationship to psychological security among newlyweds in Karak Governorate - Dmour, Rasha Abdel Hamid (Journal of Educational and Psychological Sciences, 2021)
The present study aimed to identify the level of attachment of newlyweds and the type of attachment they have. It also aimed to discover the level of psychological security of newlyweds. The study also aimed to discover the relationship between the nature of attachment and psychological security of newlyweds, and the sample consisted of (158) married women. Recently, the duration of their marriage ranged between married less than three years ago and living in Karak Governorate in the Hashemite Kingdom of Jordan, and two scales were developed through theoretical literature and previous studies. The first scale is the attachment scale and consists of four dimensions: safe attachment, anxious attachment, and avoided attachment, and confused attachment, and a measure of psychological security, the study was applied to respondents in the year (2018).The results of the study found that the level of attachment of wives was average, and the attachment level among newlyweds was in the following order: secure attachment, then confused attachment, then vacillating attachment, then avoided attachment, and that the level of psychological security of newlyweds was average, and that there is a relationship Positive relationship between safe attachment and psychological security, while there was a negative statistically significant relationship between avoided and confused attachment with psychological security, and there was no relationship between fluctuating attachment and psychological security, and also the results of the study concluded that the type of attachment varies according to the age group and in favor of the younger age group It differs according to the educational level and in favor of the less educated level.Based on the results of the study, some recommendations were made, including: Working to involve newlyweds in counseling courses to help them in good psychological adjustment, working to meet the need for psychological security of newlyweds by interviewing them to identify their concerns.
Keywords: the nature of attachment; psychological security; newly married women